Turn-Taking Strategies of Nathan Feuerstein’s Interview - Dwi Rahayu; Pajar Pajar (Doctoral Program of Social Science Pasundan University, 2026)
Turn-taking is a component that maintains effective flow of information in a conversation. This study aims to analyze the turn taking strategies used in Nathan Feurstein’s interview in YouTube video ‘NF on new album 'Hope', working with Julia Michaels and how OCD affected his creative process’. The objective of this study is to identify the types of turn-taking strategies comprising Turn Construction Units (TCUs), Adjacency Pairs, and Preference Organization in the interview. A descriptive qualitative method was applied, employing the theoretical framework of Sacks, Schegloff, and Jefferson (1974) of Turn Taking Strategies. Data consisted of spoken utterances that is transcripted and analysed for the types of Turn Taking Strategies. The findings of this research reveal the occurrence of seven Turn Construction Units (TCUs), five Adjacency Pairs, and eight instances of Preference Organization identified in the analyzed conversation. The equal number of finding shows that the speakers effectively manage using turn taking effectively, balanced flow of conversation by nondomination of one speaker and employed conversational strategies that promoted mutual understanding and social harmony. These findings contribute to conversational analysis by offering insights into the practical application of turn-taking strategies in real-world communication, particularly in media interviews